Analysis of Domestic Tourist Travel Preferences Post-Covid-19 Pandemic - L.K. Herindiyah Kartika Yuni (Politeknik Negeri Bali, 2020)
The purpose of this study was to reveal the travel preferences of domestic tourists post-covid-19 pandemics. Data was collected through questionnaires using purposive random sampling. The respondents were 300 people ranged from 17 to 55 years old. Besides surveys, data was obtained through literature studies. It is analyzed using quantitative descriptive analysis. The analysis of tourist characteristics showed most of the age group travel in post-pandemic ranged from 26-45 years old. Observed from gender, as much as 52.2% of female tourists were dominating this criterion. In education level, the majority are undergraduates (49.1%). Based on region, majority of tourist come from Bali (54 %). Private employees dominate as much as 38.07%. The results showed that most respondents made regular trips 1 to 5 times a year (90.5%). They chose to travel immediately after the pandemic, which was between 1-3-month (35.7%). Finances and travel costs were very important concerns for almost 71.3% of tourists. As much as 63.3% of tourist chose to travel with a partner and airplane were the main choice (71%). They prefer cheap homestays rather than expensive hotels (48.6%). The type of tourism chosen were dominated by nature tourism (58.7%). Most tourists preferred to arrange their own trips than the other option (47.7%). It is expected that the results will become a consideration for tourism industry managers to determine the right products and services based on tourists’ preferences who will come in post-pandemic.